2016
DOI: 10.1093/infdis/jiw515
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Vaccine-Type Human Papillomavirus Prevalence Among Women in the United States, 2009–2012

Abstract: Between 2009 and 2012, the proportion of young women in the United States completing the human papillomavirus (HPV) vaccine doubled. To understand how quickly this increased uptake is affecting women in the United States, we evaluated the prevalence of vaccine-type (VT) HPV strains among young women in national data sets from 2009-2010 and 2011-2012. Among 18-26-year-old women, the prevalence of VT HPV decreased markedly over a short interval, from 15.4% in 2009-2010 to 8.5% in 2011-2012 (prevalence ratio, 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…23 Previous comparisons of HPV vaccine types (HPV 6, 11, 16, and 18) in the pre- and post-vaccine periods and in vaccinated and unvaccinated women have revealed a decrease in HPV prevalence among younger females. 8,11,2428 For example, a recent analysis of the National Health and Nutrition Examination Survey data reported a vaccine effectiveness of 83%, and demonstrated that from the pre-vaccine era (2003–2006) to the vaccine era (2011–2014), vaccine-type prevalence decreased by 89% and 34% among vaccinated and unvaccinated females aged 14–24 years, respectively. 26 The impact of HPV vaccination on high-grade cervical cancer lesions (cervical intraepithelial neoplasia grades 2 and 3 and adenocarcinoma in situ) has also been previously examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Previous comparisons of HPV vaccine types (HPV 6, 11, 16, and 18) in the pre- and post-vaccine periods and in vaccinated and unvaccinated women have revealed a decrease in HPV prevalence among younger females. 8,11,2428 For example, a recent analysis of the National Health and Nutrition Examination Survey data reported a vaccine effectiveness of 83%, and demonstrated that from the pre-vaccine era (2003–2006) to the vaccine era (2011–2014), vaccine-type prevalence decreased by 89% and 34% among vaccinated and unvaccinated females aged 14–24 years, respectively. 26 The impact of HPV vaccination on high-grade cervical cancer lesions (cervical intraepithelial neoplasia grades 2 and 3 and adenocarcinoma in situ) has also been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on the HPV vaccine have investigated the vaccine’s impact on the prevalence of the virus and high-grade cervical lesions. 711 To date, no study has examined trends in cervical cancer incidence before and after the HPV vaccination was introduced among young females who may have been vaccinated. An ecologic study comparing cervical cancer incidence among young females before and after HPV vaccine introduction provides insight into whether HPV vaccination has contributed to potential changes in cervical cancer incidence, particularly among younger girls who may not routinely undergo screening to detect cervical lesions.…”
Section: Introductionmentioning
confidence: 99%
“…8,[14][15][16][17][18][19][20][21] However, there is evidence that HPV prevalence is decreasing in the US since the HPV vaccine was introduced, and limited evidence of herd immunity has also been demonstrated. [22][23][24] Unfortunately, although we can anticipate decreasing HPV-related cancer rates across the US, it is likely that disparities will continue due to uneven vaccination rates across geographies and race/ethnicity. Several factors contribute to uneven HPV vaccination, and careful surveillance is needed to evaluate how variations in HPV vaccination affect cervical cancer incidence and disparities over the next 2 to 3 decades.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the USA, coverage of the 4vHPV vaccine has been much lower, at 40% for females and 22% for males; yet despite this, national impact studies from the USA 4 years after the introduction of HPV vaccines noted a 56% decrease in HPV vaccine types (from cervical-vaginal samples from 14- to 19-year-olds) 31, 32 . Although the early vaccination initiation uptake rate was low (at 17%) for females 19 to 26 years old in 2009, by 2012 the uptake in the USA had doubled to 34%, resulting in a further 45% decrease in the prevalence of vaccine-type HPV 33 , or an overall 64% decrease in vaccine-type HPV prevalence after 6 years 32 . A less marked, but still significant, reduction of 34% prevalence over the same time frame was noted in the 20- to 24-year-old group 32 .…”
Section: Introductionmentioning
confidence: 99%